An elderly low-grade fibromyxoid sarcoma patient with early postoperative recurrences and metastases: a case report and literature review - Zhang, Xiaoyue; Qiu, Yongkang; Zhang, Jixin; Chen, Zhao; Yang, Qi; Huang, Wenpeng; Song, Lele; Kang, Lei (Frontiers in Medicine, 2024)
Background: Low-grade fibromyxoid sarcoma (LGFMS) is a rare type of soft tissue sarcoma that often involves the deep soft tissue of the extremities and trunk in young and middle-aged adults. It is uncommon in the elderly. Here we discuss a case of LGFMS in an elderly patient who had recurrence and metastasis within 2 years of resection of the primary tumor.Case report: A 71-year-old LGFMS patient was presented with a mass in the left forearm accompanied by pain and numbness from the left upper arm to fingers. The patient subsequently underwent 3 surgical resections, although she had 3 recurrences within 6 months after the initial diagnosis. Considering the malignant biological behavior of the tumor, an amputation at 5 cm above the elbow was eventually performed. However, recurrence in the extremity of the stump and chest wall metastasis were observed two years after amputation. Then resection of the metastases, radiotherapy and particle implantation therapy were performed. The patient is currently undergoing follow-up and has no evidence of recurrence.In our case, multiple early postoperative recurrences may be associated with a positive margin at initial operation. The patient underwent a total of 5 operations including local resection of the primary tumor, twice wide resections, amputation and metastatic surgery with 4 early postoperative recurrences and metastases within 4 years, suggesting that LGFMS may have highly invasive biological behavior. Our case demonstrated that early aggressive surgical treatment is recommended for LGFMS patients with a positive margin at initial operation and patients who had recurrence even after wide resection rather than local resection. Further research is needed to develop more effective treatment options for rapidly progress and highly aggressive LGFMS.